Pronunciation Acquisition Patterns of Learners with Different Starting Levels - Smakman, Dick; de France, Thomas (Research in Language, 2015)
This study described the results of an investigation into the effect of an intensive 12-week pronunciation course in British English which 30 Dutch female 1st-year university students of English took. They read out the same text before and after the course. Each student’s ‘before’ and ‘after’ tests were recorded. Before analysis of their results, students were split up into three groups on the basis of their general starting level: high, intermediate and low. The analysis involved a before- and after comparison of the pronunciation of eleven different phonemes: /æ, ɒ, ɔː, ʌ, ʊ, d, θ/, medial /t/, coda /r/, and syllable-final /d, v/.The analysis was done by means of both auditory and acoustic analysis. Four degrees of success (or lack thereof) were defined. The results show that the consonants required the least effort, as they were already relatively acceptable before the course started. This was true of students in general, regardless of initial starting level. The three levels of students are most distinguishable on the basis of the development of the consonants during the course. The weaker students’ consonants in particular benefitted from the course.The research revealed that initial level can be used to predict the trajectory of improvement. A general conclusion is that teachers may recognise types of students before the course starts and subject them to different types of teaching.